2019
DOI: 10.3390/ma12091415
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Concrete Pumping Behavior via Local Flow Simulation with Discrete Element Method

Abstract: The use of self-consolidating concrete and advanced pumping system enables efficient construction of super high-rise buildings; however, risks such as clogging or even bursting of pipeline still exist. To better understand the fresh concrete pumping mechanisms in detail, the discrete element method is employed in this paper for the numerical simulation of local pumping problems. By modeling the coarse aggregates as rigid clumps and appropriately defining the contact models, the concrete flow in representative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…The results showed that particles tend to aggregate at the bend. Similarly, Zhang Y [13] found that concrete fibers gather at the bend. CFD-DEM methods can be adversely affected by a considerable rigid body under mesh motion conditions.…”
Section: Introductionmentioning
confidence: 85%
“…The results showed that particles tend to aggregate at the bend. Similarly, Zhang Y [13] found that concrete fibers gather at the bend. CFD-DEM methods can be adversely affected by a considerable rigid body under mesh motion conditions.…”
Section: Introductionmentioning
confidence: 85%
“…Numerical models can help in understanding the SIPM during pumping and characteristics of LL, as well as predicting pumping pressures. However, such tools have so far been simplified by the assumption of either a single-fluid homogeneous medium [23,24,25,28,34] or discrete granular elements [35]. In the case of concretes with high granular fractions, the interactions between aggregate and paste are crucial.…”
Section: Pumpingmentioning
confidence: 99%
“…e experimental, analytical, and numerical results found that the behavior of the lubricating layer is similar to that of mortar in terms of rheology. Zhan et al [15] used the DEM to numerically simulate the local pumping problem and explored the influence of a series of factors on the local pumping performance, which were related to the pipe geometry, aggregate geometry, and pumping conditions. Shengqiang et al [16] used a computational fluid dynamics-discrete element method (CFD-DEM) coupling model to explore the influence of structural parameters and inclination angles of tapered pipes, elbows and their combinations on pressure loss, and proposed a pump truck conveying pipeline.…”
Section: Introductionmentioning
confidence: 99%